Treatment of central serous chorioretinopathy with beta-blocker metipranolol - Chrapek, Oldrich; Jirkova, Barbora; Kandrnal, Vit; Rehak, Jiri; Sin, Martin (Biomedical papers, 2015)
Aim: The purpose of this study was to evaluate the effect of the systemically administered betablocker metipranolol on the course of central serous chorioretinopathy (CSC).Methods: A prospective double-blind study involving 48 patients with a first attack of CSC not exceeding two weeks and who agreed to the follow-up ophthalmology examinations every week. The group was divided into a metipranolol group (n=23), receiving 10 mg of drug twice per day and a placebo group (n=25). The outcome measure was time in weeks from drug intervention (metipranolol vs. placebo) to reattachment of macula neuroepithelium.Results: There was no statistically significant difference in duration of CSC in patients who used metipranolol and those who used placebo (P=0.341).Conclusions: In a prospective double-blind study, we found no effect of the betablocker metipranolol on the duration of central serous chorioretinopathy.
Keywords: betablocker; central serous chorioretinopathy; metipranolol